Caring Is Not a Conflict of Interest: Indigenous Care Values Versus Institutional Policies. - Punchard, Sierra (International Journal for Human Caring, 2025)
This article examines how health care policies that prohibit providers from caring for family members or others with whom they have relationships conflict with Indigenous approaches to care. These policies, framed as safeguards against conflicts of interest, are rooted in colonial models that privilege detachment and institutional control over relational accountability and community connection. Indigenous epistemologies, which view care as relational, holistic, and reciprocal, challenge this Western paradigm. Drawing on Indigenous worldviews, policy analysis, and personal narrative, this article shows how prohibiting Indigenous providers from caring for kin and community severs trust, alienates patients, and creates ethical dilemmas. Such policies fail to recognize that connection is a source of strength that fosters cultural safety and better health outcomes. A paradigm shift is needed: caring is not a conflict of interest but the foundation of life, healing, and community. Reforming restrictive policies is essential to achieving culturally safe, ethical, and effective care.